The structure of the large magellanic cloud - Abedigamba_OP, Oyirwoth (Department of Astronomy, 2024)
This work gives an account of the study of the metallicity [Fe/H] distribution (gradient) in the oldest population in the Large Magellanic Cloud (LMC), by making use of the available RR Lyrae data from the Optical Gravitational Lensing Experiment III (OGLE III). RR Lyrae stars are amongst the oldest objects in the universe and they have a range in element (metal) abundances. Measuring the distribution of metallicities of RR Lyrae stars in a galaxy gives one clues to the origin of galaxies. It is known that the pulsation periods of RR Lyraes is broadly correlated with their metallicity. This fact has been used for investigating the metallicity distribution of RR Lyrae stars in the LMC. I have found an indication that the proportion of metal poor RR Lyrae stars increases with distance from the centre of the LMC. In addition, an attempt was made to improve the metallicity-period relation by introducing the Fourier parameters, but this was unsuccessful. Lastly, a comparison is made with estimates of metallicity gradients of other LMC populations.